887 Analysing the offender driver behaviour: recidivism, just the tip of the Iceberg?. (1st September 2016) - Castro, C; García-Fernández, P; Ventsislavova, P; Esiman, E; Crundall, D
Abstract : Background: The Subjective Risk Estimation (SER) depends on the own driving skills self- assessment and the calibration made between the benefits and cost involved in this risk at the moment of driving. Offender drivers' assumption of higher risk could be related with a more general factor that also involves the assumption of higher risk in other facets of their lives that could derive in drugs taking or other kind of additions. Deficient SER could be considered as a TRAIT, a higher proneness or disposition that only some drivers could show as another characteristic of their personality (measured with the DOSPERT (Domain-Specific Risk Taking ). It could also be possible to establish a relation with other personality measures related to Anger or Aggressive Driving, measured with DAS ( Driving Anger Scale) . Methods: The Subjective Risk Estimation (SER) is measured with the DOSPERT (Domain-Specific Risk Taking Scale ). The Anger to Aggressive Driving is measured with DAS ( Driving Anger Scale) . Results: In this work we would like to find out if could deficient SER be considered as a TRAIT of personality and some drivers could show a higher proneness to it (i.e. offender drivers) and if does deficient SER take part of a more general pattern of behaviour related with risk behaviour (drugs taking, alcohol consumption, and addiction to food or sex) that should be also trait to sort the problem out. Results are in progress. Conclusions: This knowledge could be useful to better understand the different profiles of drivers. To plan prevention and to settle better strategies of intervention and treatment of the specific lacks for each group of drivers, for instance, reducing aggressive driving or helping to be aware of the problem and dealing with the Anger in offender drivers.